The effect of recent competition between the native Anolis oculatus and the invasive A. cristatellus on display behavior - Claire M. S. Dufour; Anthony Herrel; Jonathan B. Losos (PeerJ, 2018)
Invasive species are a global threat to biodiversity. Cases where the invasion has been tracked since its beginning are rare, however, such that the first interactions between invasive and native species remain poorly understood. Communication behavior is an integral part of species identity and is subject to selection. Consequently, resource use and direct interference competition between native and invasive species may drive its evolution. Here, we tested the role of interactions between the recently introduced invasive lizard Anolis cristatellus and the native Anolis oculatus on variation in behavior and communication in Calibishie (Dominica). From May to June 2016, we filmed 122 adult males of both species displaying in banana farms under two contexts (allopatry and sympatry). We then recorded (i) the proportion of time spent displaying and (ii) the relative frequency of dewlap vs. push-up displays. To control for habitat variation, we measured and compared the habitat characteristics (canopy openness and habitat openness) of 228 males in allopatry and sympatry. While the habitat characteristics and total display-time did not differ between the contexts for the two species, the proportion of display-time spent dewlapping by A. cristatellus decreased in sympatry. The display of A. oculatus did not differ between the contexts, however. Shifts in microhabitat use, predation pressure, or interspecific interference are potential factors which might explain the behavioral changes in display observed in A. cristatellus. This study highlights the role of behavioral traits as a first response of an invasive species to recent competition with a closely related native species.